Chikungunya Case Classification after the Experience with Dengue Classification: How Much Time Will We Lose? - Cavalcanti, Luciano Pamplona de Góes (Am J Trop Med Hyg, 2020)
In 2013, cases of chikungunya virus (CHIKV) infection were first detected in the Caribbean. Chikungunya virus rapidly spread through Central and South America, causing explosive outbreaks in naive populations. Since its emergence in 2004, the number of case and series reports describing severe, atypical manifestations seen in chikungunya patients has increased substantially, calling into question whether clinicians and health services are failing to diagnose these atypical cases because of not only insufficient knowledge but also limitations in the case classification. Although this classification based on the duration of the musculoskeletal (acute, subacute, and chronic forms) complaints helped guide therapeutic approaches directed to these manifestations, patients presenting severe or complicated forms, which are less frequent but produce most of the fatal outcomes, were not properly addressed. In Brazil and the Caribbean, a clear temporal and spatial association between excess overall mortality and the occurrence of chikungunya epidemics has been shown, supporting the hypothesis that many of these excess deaths were a consequence of CHIKV infections. Thus, accumulated experience has highlighted that the current chikungunya case classification does not encompass the actual needs presented by certain cases with atypical features nor does it contribute to early detection and management of potentially severe cases. With continued CHIKV circulation in three continents and recent reemergence in Asia and Europe, we need a classification that is prospective and informed both by initial clinical presentation and by progression of signs and symptoms.